Advancing archaeal research through FAIR resource and data sharing, and inclusive community building - Solenne Ithurbide; Nicole Buan; Stefan Schulze (Communications Biology)
Abstract Over the last two decades archaeal research has expanded into a wide-ranging research field, driven by a fairly small research community. Archaea are now recognized as important players in the One-Health approach and expertise on the biology of archaea has become crucial in the study of a broad range of topics and environments, including the host-associated microbiomes, major nutrient cycles, greenhouse gas metabolism, the cell biology and origin of eukaryotes, adaptation of life to extremes, as well as various biotechnological applications. Here, we summarize existing resources and ongoing efforts in the engaged broader archaeal scientific community to accelerate research and resource sharing guided by FAIR (findable, accessible, interoperable, reusable) data-sharing principles. We highlight ongoing community efforts that: (i) aim to share protocols and best practices for working with archaea (e.g. ARCHAEA.bio), (ii) combine large ‘omics datasets for the dissemination of unified, system-wide results (e.g. Archaeal Proteome Project, KBase) and (iii) provide opportunities for scientists to present their work in a supportive environment and to forge connections and collaborations (e.g. Archaea Power Hour). Together, these resources and projects promise to spur and cross-fertilize research, making archaeal research more accessible to a broader and more diverse audience.